Kaya slice: Innovation of traditional food for breakfast-on-the-go - Halimah, Ab. Rahim; Hasan, Ahmad (2021)
A transformation of custard-like texture(traditional kaya) into sliceform that is more convenient(on-the-go) and nutritious.